Education for Sustainable Development through International Collaboration. A Case Study on Concepts and Conceptual Change of School‐Students from India and Austria on Gender Equality and Sustainable Growth - Martin Dür; Lars Keller (MDPI AG, 2018)
Dealing with the great challenges of the 21st century requires far reaching changes in the lifestyle and perceptions of humans to ensure an appropriate quality of life for all, now and in the future. To provide people with the necessary competencies, the UN initiated the Education for Sustainable Development (ESD) program. The two-year research-education, cooperative project ‘AustrIndia-4QOL’ aims to contribute to the goals of ESD. It is based on a collaboration between students from schools in Austria and India on the topics of quality of life, sustainability and global justice. The purpose of this particular case study is to explore the effects of a weeklong face-to-face collaboration in the final part of the AustrIndia-4QOL project. Therefore, it is examined whether or not Austrian and Indian students’ concepts regarding the Sustainable Development Goals ‘Gender Equality’ and ‘Decent Work and Economic Growth’ change as a consequence of encountering differing perspectives. Short texts written by the students at the beginning and at the end of this collaboration, according to guiding questions, form the basis for a qualitative content analysis. The findings illustrate that the students’ awareness increased and their evaluation of topics related to the discussed sustainable development goals changed.